2023
DOI: 10.3390/ijms24097834
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Pyrazoles in Medicinal Chemistry: A Review

Abstract: A pyrazole nucleus is an easy-to-prepare scaffold with large therapeutic potential. Consequently, the search for new pyrazole-based compounds is of great interest to the academic community as well as industry. In the last ten years, a large number of papers and reviews on the design, synthesis, and biological evaluation of different classes of pyrazoles and many pyrazole-containing compounds have been published. However, an overview of pyrazole derivatives bearing a free amino group at the 3, 4, or 5 position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…26a Aminopyrazoles are even more important and show a variety of medicinal applications. 26b For instance, they are ligands for receptors or enzymes, such as p38MAPK, and different kinases, such as COX and others. In addition, they possess antibacterial and antiviral activity.…”
Section: Reactions Of Simple Nitro-substituted Heterocyclesmentioning
confidence: 99%
“…26a Aminopyrazoles are even more important and show a variety of medicinal applications. 26b For instance, they are ligands for receptors or enzymes, such as p38MAPK, and different kinases, such as COX and others. In addition, they possess antibacterial and antiviral activity.…”
Section: Reactions Of Simple Nitro-substituted Heterocyclesmentioning
confidence: 99%
“…Pyrazole, a five-membered heterocyclic ring, is an important scaffold with diverse pharmacological activities such as anticancer, , antimicrobial, , antimalarial, anti-inflammatory, and other activities. Particularly, the pyrazole ring also plays a crucial role in the development of chemical fungicides. For example, among the 24 commercial SDHI fungicides, up to 12 commercial SDHI fungicides possess a pyrazole fragment (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazole scaffold represents a privileged substructure in medicinal chemistry research and a number of pyrazole derivatives have been evaluated as effective compounds in different therapeutic areas [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], including infectious diseases [ 17 , 18 ] and also against MRSA [ 19 ]. In previous studies, pyrazole derivatives I ( Figure 1 ) showed significative antibacterial activity against Gram-positive antibiotic-resistant strains [ 20 ].…”
Section: Introductionmentioning
confidence: 99%